Analyzing the Relationship between Digital Game Addiction and Developmental Levelss Aged 4-6 Years Old - Aida Novitasari; Ananda Zara Eka Putri; Enung Mardiyana Hidayat; Adin Muafiroh; Indriatie Indriatie (International Journal of Advanced Health Science and Technology, 2023)
digital era is experiencing very rapid development, especially the use of gadgets and this is in demand by all age levels, including pre-school age children. This has an impact on the level of child development in the form of delays in the level of development. The purpose of this study was to determine the relationship between game addiction and the level of development of children aged 4-6 years. The research design is cross sectional, the sampling technique used is a total sampling of 38 children at the Handayani Kindergarten in Surabaya, the independent variable is addiction to playing games, the dependent variable is the level of development of children aged 4-6 years. The analytical test used was spearman rho = 0.01. The results of the study show that there is a relationship between addiction to playing gadgets with the level of development of children aged 4-6 years with p value = 0.000 <0.05. Parents are expected to know the impact of gadget addiction and be able to provide education and assistance to their children when using gadgets, there are rules that must be agreed between children and parents regarding the duration of gadget use. Facilitates the game manually, introduces interesting traditional games.